2017
DOI: 10.1371/journal.pone.0188358
|View full text |Cite
|
Sign up to set email alerts
|

The association between the nicotinic acetylcholine receptor α4 subunit gene (CHRNA4) rs1044396 and Internet gaming disorder in Korean male adults

Abstract: The primary aim of this study was to investigate the genetic predisposition of Internet gaming disorder (IGD), and the secondary aim was to compare the results to those of alcohol dependence (AD). Two independent case-control studies were conducted. A total of 30 male participants with IGD, diagnosed according to the 5th edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) criteria, and 30 sex-matched controls participated in study 1. We designed targeted exome sequencing (TES) to test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 68 publications
1
10
0
1
Order By: Relevance
“…The role of nAChRs in impulsive behavior has been discussed previously (215). In humans, polymorphism in the α4 subunits of the nAChRs (CHRNA4) was associated with pathological gambling in Korean gamblers (216).…”
Section: Pharmacological Targets To Treat Psychostimulant-induced Cogmentioning
confidence: 95%
“…The role of nAChRs in impulsive behavior has been discussed previously (215). In humans, polymorphism in the α4 subunits of the nAChRs (CHRNA4) was associated with pathological gambling in Korean gamblers (216).…”
Section: Pharmacological Targets To Treat Psychostimulant-induced Cogmentioning
confidence: 95%
“…Impaired response inhibition is an important issue in behavioral addiction. These combined results suggest that the nicotinic acetylcholine receptor may play a role in IGD by modulating the dopaminergic pathway and may affect the addiction phenotype, such as response inhibition (Jeong et al, 2017).…”
Section: Polymorphism Gene In Internet Addictionmentioning
confidence: 87%
“…As was supported by numerous studies, the said genetic variants were also associated with a predisposition to depression—the most prevalent comorbid disorder in Internet-addictive subjects [64]. rs1044396 (nicotinic acetylcholine receptor subunit alpha 4 ( CHRNA4 ) gene): a small sized case-control study by Montag et al [65] showed the presence of an association with the CC genotype of the polymorphism rs1044396, which is also related to nicotine addiction and attention disturbances.rs2229910 (neurotrophic tyrosine kinase receptor type 3 ( NTRK3 ) gene): A pilot study by Jeong et al [66] was aimed at a specific exome and involved 30 adults with Internet addiction and 30 healthy subjects. The research included studying 83 polymorph regions and revealed statistically convincing associations with only one region: rs2229910.…”
Section: Genetics Of Internet Addictionmentioning
confidence: 99%
“…rs2229910 (neurotrophic tyrosine kinase receptor type 3 ( NTRK3 ) gene): A pilot study by Jeong et al [66] was aimed at a specific exome and involved 30 adults with Internet addiction and 30 healthy subjects. The research included studying 83 polymorph regions and revealed statistically convincing associations with only one region: rs2229910.…”
Section: Genetics Of Internet Addictionmentioning
confidence: 99%